2022
DOI: 10.1200/jco.2022.40.36_suppl.359881
|View full text |Cite
|
Sign up to set email alerts
|

INTRIGUE: A phase III, randomized, open-label study to evaluate the efficacy and safety of ripretinib versus sunitinib in patients with advanced gastrointestinal stromal tumor previously treated with imatinib

Abstract: 359881 Background: Sunitinib is approved for advanced gastrointestinal stromal tumor (GIST) after imatinib failure. Ripretinib, a broad-spectrum KIT and PDGFRA switch-control tyrosine kinase inhibitor (TKI), is indicated for the treatment of adult patients (pts) with GIST who received prior treatment with 3 or more TKIs, including imatinib. We compared the efficacy and safety of ripretinib vs sunitinib in pts with advanced GIST who progressed on or were intolerant to imatinib. Methods: This multicenter, globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…The phase III trial (INVICTUS) confirmed the role of ripretinib as the fourth-line treatment based on a median PFS of over 6 months compared to only 1 month in the placebo arm. The preliminary results of the phase III INTRIGUE trial showed that ripretinib is not superior to sunitinib as a second-line TKI for patients with GIST in terms of progression-free survival [ 26 ]. The relative safety profile similar to imatinib provides heavily pretreated patients a feasible drug of choice.…”
Section: Systemic Treatments For Advanced/metastatic Gistmentioning
confidence: 99%
“…The phase III trial (INVICTUS) confirmed the role of ripretinib as the fourth-line treatment based on a median PFS of over 6 months compared to only 1 month in the placebo arm. The preliminary results of the phase III INTRIGUE trial showed that ripretinib is not superior to sunitinib as a second-line TKI for patients with GIST in terms of progression-free survival [ 26 ]. The relative safety profile similar to imatinib provides heavily pretreated patients a feasible drug of choice.…”
Section: Systemic Treatments For Advanced/metastatic Gistmentioning
confidence: 99%
“…A total of 453 patients with GIST were enrolled in this study, where 226 patients received continuous dosing of 150 mg of ripretinib and 227 patients received continuous dosing of 50 mg of sunitinib (4-week on and 2-week off). Although the study did not meet its primary endpoint, progression-free survival (PFS) in ripretinib treated patients was not superior those treated with sunitinib, but there were significant advantages in ORR and safety profiles ( 42 ). In all population, mPFS was similar in patients treated with ripretinib compared to those treated with sunitinib: 8.0 months vs 8.3 months (HR = 1.05, 95% CI 0.82 to 1.33).…”
Section: Next-generation Tkis In Gist: Ripretinib and Avapritinibmentioning
confidence: 98%
“…In the INTRIGUE STUDY, the safety profile of ripretinib was improved compared to that of sunitinib, with a lower incidence of grade 3/4 AEs (26.5% vs 55.2%). For grade 3/4 AEs with an incidence of ≥2%, the incidence of these events was also lower in the ripretinib group than in the sunitinib group ( 42 ).…”
Section: Next-generation Tkis In Gist: Ripretinib and Avapritinibmentioning
confidence: 98%
“…Ripretinib has also been assessed compared to sunitinib in the phase III INTRIGUE study in patients with advanced GIST after treatment with imatinib. PFS was not statistically different between the ripretinib and sunitinib arms, and median OS was not reached in either arm [ 55 ].…”
Section: Treatmentmentioning
confidence: 99%